The Impact of IKM on Teacher Competence and Professionalism - Radenrara Sutaris (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
This study aims to analyze the impact of Implementation of the Independent Curriculum (Indonesia: Implementasi Kerikulum Merdeka/IKM) on teacher competence, professionalism and teacher professional development. This research is an exploratory research, namely research that seeks to explore the causes and impacts and factors that influence it. The results showed that the IKM had a significant impact on the competence, professionalism and development of the teaching profession. Based on competence, the impact of IKM on teacher competence states that 47% of teachers are highly competent and 51% of teachers are competent. Judging from the professionalism of teachers in teaching, it is proven that 97% of teachers understand and master the assessment of students, 99% of teachers are able to design learning and are very good at learning concepts and materials. Meanwhile, from the development of the teaching profession, most teachers have the habit of self-reflection and have emotional maturity. Teachers also have a high concern for students and have a spirit of mutual cooperation.